2015
DOI: 10.3750/aip2015.45.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Cannibalism in cultured Eurasian perch, Perca fluviatilis (Actinopterygii: Perciformes: Percidae)—Implication of maternal influence, kinship, and sex ratio of progenies

Abstract: Król J., Dauchot N., Mandiki S.N.M., Van Cutsem P., Kestemont P. 2015. Cannibalism in cultured Eurasian perch, Perca fluviatilis (Actinopterygii: Perciformes: Percidae)-Implication of maternal influence, kinship, and sex ratio of progenies. Acta Ichthyol. Piscat. 45 (1): 65-73.Background. Intra cohort cannibalism is one of the main factors that affects the growth and survival of cultured fishes, especially in the larval and juvenile stages. Cannibalism is mainly influenced by extrinsic factors, but intrinsic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…the ability of a genotype to produce more than one phenotype when exposed to different environments; Pigliucci et al 2006;Kelly et al 2012) is an alternative explanation of the observed behavioural differentiations between populations (DeWitt and Scheiner, 2004) with behaviour reflecting the strategy adopted under the influence of environmental factors. This was suggested as the driving factor for cannibalism in P. fluviatilis (Krol et al 2015 and references therein) as well as in other species (e.g. Svenning and Borgstrøm 2005).…”
Section: Inter-populational Differentiation In Behavioural Traits Andmentioning
confidence: 93%
See 1 more Smart Citation
“…the ability of a genotype to produce more than one phenotype when exposed to different environments; Pigliucci et al 2006;Kelly et al 2012) is an alternative explanation of the observed behavioural differentiations between populations (DeWitt and Scheiner, 2004) with behaviour reflecting the strategy adopted under the influence of environmental factors. This was suggested as the driving factor for cannibalism in P. fluviatilis (Krol et al 2015 and references therein) as well as in other species (e.g. Svenning and Borgstrøm 2005).…”
Section: Inter-populational Differentiation In Behavioural Traits Andmentioning
confidence: 93%
“…Since we have no information on the parents of egg sampled, we cannot exclude the influence of maternal effects which were demonstrated in P. fluviatilis for other traits (Babiak et al 2004;Krol et al 2015).…”
Section: Inter-populational Differentiation In Behavioural Traits Andmentioning
confidence: 99%
“…The key to the further development of the production of the pikeperch is to optimize conditions for rearing both, the larval and the juvenile stages. In farmed percid fish species, intra-cohort cannibalism, besides swim bladder inflation and non-feeding behavior, is an important factor that affects survival, especially during the early life stages of fish Kestemont et al 2003;Babiak et al 2004;Hamza et al 2007; Mandiki et al 2007;Szkudlarek and Zakęś 2007;Król et al 2015). Cannibalism is intra-specific predation.…”
Section: Introductionmentioning
confidence: 99%